Peran Pelayanan Akademik dalam Meningkatkan Kepuasan Mahasiswa di STIE IBMT Surabaya - Ilham Sulaiman; Iswati Iswati; Emilia Pranata (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research was conducted to find out about "The role of academic services in increasing student satisfaction at STIE IBMT Surabaya". In accordance with the main issue raised, namely the role of academic services in increasing student satisfaction. Among other things, the quality of service, the level of student satisfaction, as well as the characteristics of student expectations for STIE IBMT Surabaya, which is the background for conducting this research, is because there is still a lot of concern regarding STIE IBMT Surabaya students' dissatisfaction with the quality of services provided. The research method used in this research is a qualitative method, there are 6 informants consisting of STIE IBMT students as partners and teaching staff and staff as partners of STIE IBMT Surabaya using primary data sources and secondary data used to collect data using observation, interviews and documentation of the data that has been collected and analyzed. The conclusion of this research is that the academic role of STIE IBMT Surabaya is very much needed and very important to increase students' sense of satisfaction significantly and positively which influences the image of the campus to become the choice of prospective new students. Meanwhile, if academics do not play a role in trying to improve service quality, it will make the campus image negative and affect the popularity of prospective new students interested in STIE IBMT Surabaya in the future.